Liturgy and life study Bible - Martens, John W. 1960-; Turner, Paul 1953- (Collegeville Liturgical Press, 2023)
Liturgy and Life Study Bible -- Foreword -- Preface -- Contributors -- Acknowledgments -- How to Use the Liturgy and Life Study Bible -- Abbreviations of Books of the Bible -- Scripture and the Liturgical Year -- The Hebrew Bible in Jewish Liturgy -- Psalms: Composed For and Used in Prayer -- Synagogue -- New Testament and the Liturgy -- Early Christian Worship -- Sacraments and the Bible -- Liturgy and Social Justice from a Biblical Perspective -- Early Israelite Worship -- Sabbath, Rest, and Worship -- Israelite Festival Calendar -- False Worship and Idolatry -- Fasting and Almsgiving -- The Priesthood (of Jesus) in Scripture and Liturgy -- Last Supper -- House Churches -- Ministers in the New Testament -- Heavenly Worship in the Book of Revelation -- Death and Funeral Rites -- The Old Testament -- Preface to the Revised New American Bible Old Testament -- Introduction to the Pentateuch -- The Book of Genesis -- The Book of Exodus -- The Book of Leviticus -- The Book of Numbers -- The Book of Deuteronomy -- Introduction to the Historical Books -- The Book of Joshua -- The Book of Judges -- The Book of Ruth -- The First Book of Samuel -- The Second Book of Samuel -- The First Book of Kings -- The Second Book of Kings -- The First Book of Chronicles -- The Second Book of Chronicles -- The Book of Ezra -- The Book of Nehemiah -- Introduction to Biblical Novellas -- The Book of Tobit -- The Book of Judith -- The Book of Esther -- The First Book of Maccabees -- The Second Book of Maccabees -- Introduction to the Wisdom Books -- The Book of Job -- The Book of Psalms -- The Book of Proverbs -- The Book of Ecclesiastes -- The Song of Songs -- The Book of Wisdom -- The Book of Sirach -- Introduction to the Prophetic Books -- The Book of Isaiah -- The Book of Jeremiah -- The Book of Lamentations -- The Book of Baruch -- The Book of Ezekiel.
"Designed from a liturgical perspective, this Bible includes major and minor essays, liturgical introductions, notes, and a table of liturgical Scriptures, detailing the intersection between biblical passages and the Catholic liturgy. Scripture texts, prefaces, and introductions are taken from the New American Bible, revised edition"--
Description based on publisher supplied metadata and other sources